Scientific and technological achievements of the oil and gas industry of Vietnam and strategies to address future challenges - Thu Hien Nguyen; Tang Son Nguyen; Thanh Tung Dang (Vietnam Journal of Science, Technology and Engineering, 2017)
Over more than 40 years of the Vietnam National Oil and Gas Group (PVN) development, Science and Technology has been played a very important role and significantly contribute to the success of PVN in all core business areas. This paper reviews the achievements of Science & Technology activities of PVN so far as well as point outs key strategies to address future challenges of oil & gas industry in Vietnam in order to improve productivity, quality, production, business efficiency, and to achieve sustainable development.